2021
DOI: 10.21203/rs.3.rs-479001/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Awareness, Uptake and factors associated with NHIF uptake in Western Kenya: A case of 4 counties - Busia, Trans Nzoia, Vihiga and Siaya

Abstract: Background Kenya is in the process of implementing universal health care whose success and sustainability will be determined by its funding mechanism and by uptake of National Hospital Insurance Fund (NHIF) by its populace. Unfortunately, NHIF enrollment is currently voluntary hence geared to those in formal employment who represent only 16.4% of the population. To improve the voluntary uptake of the scheme, it is important to have increased awareness as well as implement strategies that address factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The positive effect of the higher education levels enhances the health seeking behavior of individuals, better knowledge and understanding about the effects of illness on health care expenditure. This finding was supported by that higher level education is associated with enrolment into health insurance (Fadlallah et al, 2018;Mwaura, et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…The positive effect of the higher education levels enhances the health seeking behavior of individuals, better knowledge and understanding about the effects of illness on health care expenditure. This finding was supported by that higher level education is associated with enrolment into health insurance (Fadlallah et al, 2018;Mwaura, et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…The implication of the association between wealth and insurance uptake for settings like Malawi would be to consider a minimal amount of health insurance schemes for the less privileged since the less privileged are the most marginalized in uptake of health insurance. Persons with low education level have lower uptake of health insurance as observed in other similar settings like Kenya [20] [24] [25]. Level of education proxies literacy level therefore people with little knowledge and understanding on universal health care have low use of health insurance [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study in SSA by Barasa et al found that wealthier individuals were more likely to have a health insurance compared to those with less income [2]. Generally, the higher an individual’s wealth level is, the more likelihood he will participate in a health care program in SSA [2] [19] [20] and this is similar to what was observed in China, Spain and USA [18] [21] [22] [23] [24]. The implication of the association between wealth and insurance uptake for settings like Malawi would be to consider a minimal amount of health insurance schemes for the less privileged since the less privileged are the most marginalized in uptake of health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the accreditation status varied among clinics and higher-level facilities, potentially impacting service uptake 43 . Additionally, individuals diagnosed with chronic illnesses exhibited a higher likelihood of selecting healthcare providers and utilizing services, with private providers restricted to speci c service categories compared to government hospitals 24 .…”
Section: Discussionmentioning
confidence: 99%